Ethnomedicinal uses, phytochemistry, and pharmacology of the genus Sarcophyte: a review - Jared Misonge, Onyancha; Gervason Apiri, Moriasi; James Onsinyo, Meroka; Samuel Murigi, Wainaina; Geoffrey Ogeto, Sengera; Vincent Obaga, Nyandoro (Frontiers in Pharmacology, 2024)
Although medicinal plants have been used since antiquity to prevent and treat various diseases among ethnic communities, only a few have been documented scientifically. Therefore, due to their rare availability and a dearth of comprehensive scientific information, we reviewed the ethnomedicinal uses, phytochemistry, and pharmacologic activities of plants within the Sarcophyte genus. To do this, we used specific search terms and phrases to obtain relevant information from online sources published in English from 2000 to July 2023. The findings showed there are only two plants in the Sarcophyte genus (Sarcophyte sanguinea Sparrm. and Sarcophyte piriei Hutch.) and are used traditionally to treat a wide range of diseases, especially cancer, disorders of the skin, gastrointestinal and urinogenital tracts in humans, and to manage diseases afflicting animals in ethnoveterinary practices. It was noted that thirteen secondary metabolites have been isolated from the two plants, and the most prominent are flavonoids (diinsininol, diinsinin, and naringenin). Antioxidant activity of S. piriei is reported based on scavenging the 2,2-diphenyl-1-picryl hydrazyl (DPPH) (IC50: 4.26 ± 0.22 µg/ml) and 2 -2'-Azino-di-[3-ethylbenzthiazoline sulfonate (ABTS) radicals (IC50: 4.62 ± 0.14 µg/ml), chelating iron (IC50: 1.82 ± 0.01 µg/ml, 3.50 ± 0.09 µg/ml), and nitric oxide (IC50: 9.97 ± 0.88 µg/ml, 9.09 ± 0.11 µg/ml). The methanolic stem extracts of S. piriei possess antimicrobial activity against Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Vibrio fluvialis, and Enterococcus avium, with minimum inhibitory concentration (MIC) values ranging from 0.16 mg/ml to 0.625 mg/ml, and minimum bactericidal concentration (MBC) of 1.25 mg/ml to 5 mg/ml. Cytotoxic effects of the extracts from the two plant species has also been demonstrated. The S. piriei possess therapeutic potential as evidenced by the inhibitory effects of the aqueous rhizome extract on edema (1000 mg/kg) and prostaglandin synthesis (IC50 = 0.2 mg/mL). Besides, diinsininol and diinsinin, isolated from S. sanguinea inhibited prostaglandin synthesis (IC50: 9.20 µM, 13.14 µM) and platelet-activating factor-induced exocytosis. Therefore, based on this review, further scientific research is still required to demystify the links between traditional medicine uses, various secondary metabolites, and the pharmacology of the two plants.